Catching the tip of the iceberg – Evaluation of sample preparation protocols for metaproteomic studies of the rumen microbiota. Issue 20 (12th May 2015) - Deusch, Simon; Seifert, Jana; Jagtap, Pratik; Griffin, Tim; Armengaud, Jean
<x xml:space="preserve">Abstract</x> Various metabolic processes are performed in the rumen caused by a complex microbiota comprising bacteria, archaea, protozoa, and fungi. Thus, the description of the active microbial fraction and their functions are of great interest for animal nutrition, biotechnology, and climatology. Metaproteomic studies of the rumen microbiota are challenged by the need of optimized sample preparation protocols in order to retrieve an enhanced amount of prokaryotic instead of plant‐ and bovine‐derived cells before protein extraction and subsequent LC‐MS/MS analysis. The present study evaluates three different protocols applied to the rumen microbiota either attached to plant fibers or present as planktonic cells. The findings of our work suggest the integration of cheesecloth‐gauze filtration in sample preparation to achieve a better protein identification ratio. Our data have been deposited to ProteomeXchange with identifier PXD001526 (http://proteomecentral.proteomexchange.org/dataset/PXD001526).